2015
DOI: 10.3389/fnins.2015.00414
|View full text |Cite
|
Sign up to set email alerts
|

I'll take the low road: the evolutionary underpinnings of visually triggered fear

Abstract: Although there is general agreement that the central nucleus of the amygdala (CeA) is critical for triggering the neuroendocrine response to visual threats, there is uncertainty about the role of subcortical visual pathways in this process. Primates in general appear to depend less on subcortical visual pathways than other mammals. Yet, imaging studies continue to indicate a role for the superior colliculus and pulvinar nucleus in fear activation, despite disconnects in how these brain structures communicate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(47 citation statements)
references
References 157 publications
2
45
0
Order By: Relevance
“…In that sense, evidence from experimentation in amphibians demonstrates that lesions in the pretectum of toads generates a behavioral syndrome in which the animal can no longer differentiate between large (predator‐like) and small (prey‐like) moving objects, resulting in the abolishment of avoidance behavior and the erratic protraction of the tongue toward large moving object; an effect attributed to the inhibitory effect of NPY on the tectal activity (Carr, ). In mammals, Gale and Murphy () recently showed that the intrinsic GABA modulation of horizontal interneurons shapes TGC selectivity to the size of moving disks.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, evidence from experimentation in amphibians demonstrates that lesions in the pretectum of toads generates a behavioral syndrome in which the animal can no longer differentiate between large (predator‐like) and small (prey‐like) moving objects, resulting in the abolishment of avoidance behavior and the erratic protraction of the tongue toward large moving object; an effect attributed to the inhibitory effect of NPY on the tectal activity (Carr, ). In mammals, Gale and Murphy () recently showed that the intrinsic GABA modulation of horizontal interneurons shapes TGC selectivity to the size of moving disks.…”
Section: Discussionmentioning
confidence: 99%
“…These different components process distinct afferent inputs and channel 160 them to parallel downstream efferent pathways, responsible for output circuits for fear of predators 161 and fear of pain (Gross and Canteras, 2012). In zebrafish, sensory input to the posterior 162 telencephalon (including Dm) suggest massive olfactory information (e.g., Miyasaka et al, 2014), 163 while visual and auditory stimuli are processed initially in the optic tectum (Northcutt, 1983;Meek, 164 1990); however, the fact that an olfactory stimulus can be associated with a visual stimulus in the 165 Dm (Ruhl et al, 2017;Lal et al, 2018) suggests the participation of a projection from the optic 166 tectum, possibly via the lateral preglomerular nucleus (Carr, 2015). Thus, in zebrafish the Dm also 167 appears to be important for learned fear, but the participation in unconditioned behavior suggests 168 that either subpopulations of the Dm process different stimuli, or that the evolutionary shift towards 169 visual and auditory stimuli in mammals displaced the massive olfactory projections that was found 170 in fish.…”
Section: /44mentioning
confidence: 99%
“…In addition to this "slow" pathways (the "forebrain circuit"), a "quick-and-dirty" pathway 577 for visual aversive stimuli is organized in the optic tectum (the "midbrain circuit") (Carr, 2015). This 578 midbrain circuit is sensitive to stimulus size and critical angle, and switches from approach (small 579 stimuli probably mean "food") to avoidance (large stimuli arriving at a specific angle probably 580 mean "predator strike").…”
Section: Tectal Circuits For Detection Of Visual Threatening Stimuli 418mentioning
confidence: 99%
See 2 more Smart Citations